Desain Habitat Buatan Kura-kura Batok (Cuora amboinensis) di Area Konservasi Eksitu Universitas Bengkulu - Fajar Eko Saputra; Bhakti Karyadi; Deni Parlindungan; Sutarno Sutarno; Aceng Ruyani; Nurma Yunita Indriyanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Cuora amboinensis has experienced a population decline of 50–80 percent in CITES Appendix II since 2000 and is currently endangered (EN) or threatened with extinction, so it is important to preserve it. Bengkulu University's ex-situ conservation involves the preservation of Sumatran turtles obtained from collectors in the Bengkulu area. This research aims to design an artificial habitat in an effort to conserve Cuora amboinensis This research method uses an ecological-based design. The research subject was Cuora amboinensis Data collection methods include field observations, literature studies, discussions with turtle conservation experts, and monitoring environmental conditions. The research instrument uses environmental sensors to measure abiotic data. Data analysis was carried out descriptively with systematic research and analysis with field findings supported by previous researchers' findings and equipped with documentation images and a table presentation of environmental sensor data. The research results explain the stages in designing an artificial habitat for Cuora amboinensis, namely site selection and design, fencing and security, adaptation and acclimation, dividing areas based on function and providing supporting biota, nest building, and monitoring environmental conditions. The conclusion of this research Overall, this habitat design provides an optimal environment for Cuora amboinensis so that it can be used as a reference for conservation.